Saamelaisjäljet Kuusamon ja Posion paikannimistössä - Räisänen, Alpo (Kotikielen Seura, 2005)
Sami influences in place names within Kuusamo and Posio (englanti)3/2005 (109)Sami influences in place names within Kuusamo and Posio Todays municipal districts of Kuusamo and Posio (originally part of Kuusamo) were not populated by Finns until after 1673, when Swedens King Charles XI issued a decree on the settlement of the Lapp areas. Until then, the area had been part of what was known as Kemin Lappi and contained two Sami winter villages: Kitka and Maaselk. With the arrival of the Finns, most of the Sami retreated eastwards and northwards, but some stayed and became assimilated with the Finnish settlers. Even before the settlers came, Finns from Ii (a large district to the southwest of Kuusamo and Posio) used to come and fish in the lakes of Kuusamo.There are many times more place names of Sami origin in Kuusamo than in the Kainuu region to the south of it, where Finnish settlement began a century earlier. Evidently the main reason for this is that a proportion of Sami inhabitants chose to remain in Kuusamo among the Finns there. There were also mixed marriages between Samis and Finns. Knowledge of ancient Sami place names was thus retained and passed on to the majority population.Most of the place names of Sami origin in Kuusamo and Posio are names of lakes and other waters, e.g. Elijrvi (< Proto-Sami *e?le- upper + Finnish jrvi lake); Irni (< Proto-Sami je?r?e? > Inari Sami jor?a open water); Jorvanjrvi (cf. Inari Sami coarvi horn, antler); Kaava, a bay in Posiojrvi (cf. Northern Sami gvva bend, curve); Kylnkoski (cf. Northern Sami geavli curve, bend); Livojrvi (cf. Northern Sami / Inari Sami Iivva- sleeping place for reindeer - the extensive sandy shores of the lake are favoured by reindeer); Paanajrvi, a big lake formerly in the Kuusamo district (< Proto-Sami *pane tooth > Northern Sami btni, Inari Btnejrvi); Sunnansalmi (cf. Inari Sami sudde unfrozen spot in the ice + Finnish salmi strait, channel); Suorajrvi, two lakes, one round and the other bifurcated (cf. Northern Sami suorri branch, ...